Acetabular Component Migration Measured Using Radiostereometric Analysis Following Revision Total Hip Arthroplasty: A Scoping Review. Issue 4 (April 2020) - Abrahams, John M.; Callary, Stuart A.; Munn, Zachary; Jang, Sung Won; Huang, Qiang; Howie, Donald W.; Solomon, Lucian Bogdan
Abstract : Radiostereometric analysis (RSA) studies of acetabular component migration following revision total hip arthroplasty (THA) have a large variation in their methodology and reporting of results, and, therefore, they may not be directly comparable. Standardization of RSA reporting is recommended. In our review of RSA studies, there was a trend for cemented acetabular components to have larger amounts of early proximal migration than uncemented acetabular components. Results regarding cemented and uncemented components should be reported separately. Cohorts that addressed larger acetabular defects were associated with a larger amount of early migration. Reporting the migration result at 1 and 2 years postoperatively may enable earlier identification of poorly performing implants.